2021
DOI: 10.1007/s11661-021-06414-2
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Capillary-Driven Fragmentation and Grain Transport with Mixed Columnar-Equiaxed Solidification

Abstract: In this study, a first attempt is made to bridge capillary-driven fragmentation and grain transport using a mixed columnar-equiaxed solidification model. Grain transport is an intrinsic feature of the employed solidification model which has been extensively investigated over the years. Regarding the capillary-driven fragmentation event, a new correlation between the number of fragments and interfacial area density of the columnar structure was recently established by Cool and Voorhees (2017) based on experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
(87 reference statements)
1
6
1
Order By: Relevance
“…In contrast, for K = 1 × 10 −23 µm 3 s −1 , r = 0.3 and n = 0.83, Equation (11) (dashed black line) exhibits a better fit to Equation (10) when the time exceeds the critical time t* in all the analyzed cases, indicating improved accuracy during the final stage of coarsening. Indeed, H. Neumann-Heyme et al [14] reported that r = 0.4 was used for the simulations and r = 0.25 for the experiments. The coarsening exponent (n) and fitting parameter (r) differed significantly in the case with an initial arm radius of r = 7 µm, compared to other cases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, for K = 1 × 10 −23 µm 3 s −1 , r = 0.3 and n = 0.83, Equation (11) (dashed black line) exhibits a better fit to Equation (10) when the time exceeds the critical time t* in all the analyzed cases, indicating improved accuracy during the final stage of coarsening. Indeed, H. Neumann-Heyme et al [14] reported that r = 0.4 was used for the simulations and r = 0.25 for the experiments. The coarsening exponent (n) and fitting parameter (r) differed significantly in the case with an initial arm radius of r = 7 µm, compared to other cases.…”
Section: Resultsmentioning
confidence: 99%
“…Ref. [14] reports a large uncertainty in the exponent (r) due to limited measurement ranges and focuses solely on solid fractions under 0.4. This suggests that (r) is mainly influenced by dendrite growth rather than coarsening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The production rate of fragments via the capillary-driven mechanism ( capillary frag N ) was calculated based on equation (2) [15,16], in which a is an alloy-dependent constant, and SV is the interfacial area density. A general expression for SV was shown in equation (3) [17], which accounted for the effects of dendrite growth, coarsening, and interface coalescence.…”
Section: Model Configuration and Calculation Methodsmentioning
confidence: 99%
“…The initial size of the formed fragments ( 0 e,frag 4) [18]. Since a spherical morphology was assumed for the equiaxed grains, the corresponding mass transfer rate ( capillary frag M ) from the columnar to the equiaxed due to the capillary-driven fragmentation can be calculated by equation ( 5) [16]. (2)…”
Section: Model Configuration and Calculation Methodsmentioning
confidence: 99%